2016
DOI: 10.1590/1809-2950/15861023042016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nordic walking on Parkinson’s disease: a systematic review of randomized clinical trials

Abstract: Several exercise modalities improve the symptoms of Parkinson’s Disease (PD). Among the variety of physical exercises, Nordic walking has been used. The aim of this study was to summarize scientific literature on effects of Nordic walking on patients with PD by a systematic review of randomized clinical trials. The following electronic databases were selected: MEDLINE by Pubmed, Cochrane, PEDro, SCOPUS and Web of Science and articles identified by manual search, without restriction of date and language. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…Un estudio Brasileño, compara la mejoría del equilibrio tras ejercicio aeróbico con marcha nórdica vs marcha libre, tras un período de 9 semanas o 12 sesiones, en personas mayores a 50 años con EP y reporta mejoría en el equilibrio, (p=0.035) en ambos tipos de marcha [22]. Da Silva et al, destacan un estudio de intervención con marcha nórdica de 6 a 24 semanas, de moderada a alta intensidad, con mejoras en el equilibrio mediante el uso del test de la escala de Berg [23]. Kurt et al, en su ensayo concluyen que la mejora del equilibrio dinámico fue significativamente mayor en el grupo que realizó Ai Chi (tipo de actividad física acuática) vs el grupo que realizó ejercicio en tierra ( p <0.001); sin embargo ambos grupos tuvieron una mejora significativa [24].…”
Section: Discussionunclassified
“…Un estudio Brasileño, compara la mejoría del equilibrio tras ejercicio aeróbico con marcha nórdica vs marcha libre, tras un período de 9 semanas o 12 sesiones, en personas mayores a 50 años con EP y reporta mejoría en el equilibrio, (p=0.035) en ambos tipos de marcha [22]. Da Silva et al, destacan un estudio de intervención con marcha nórdica de 6 a 24 semanas, de moderada a alta intensidad, con mejoras en el equilibrio mediante el uso del test de la escala de Berg [23]. Kurt et al, en su ensayo concluyen que la mejora del equilibrio dinámico fue significativamente mayor en el grupo que realizó Ai Chi (tipo de actividad física acuática) vs el grupo que realizó ejercicio en tierra ( p <0.001); sin embargo ambos grupos tuvieron una mejora significativa [24].…”
Section: Discussionunclassified
“…He was following my prescription and religiously executing his physiotherapy regime. Studies have suggested that Nordic walking [15] and physiotherapy [16] help in stabilizing gait in patients suffering from Parkinsonism as well as slow its progression. Mr. Mohan Lal would visit me every 3 months.…”
Section: Aspiration Index and Active Ageingmentioning
confidence: 99%
“…To the very best of the authors' knowledge, four systematic reviews on the benefits of NW on people with PD have been published so far. Silva et al (2016), offered preliminary conclusions since three out of the five randomised controlled trials (RCTs) reviewed showed a poor methodological quality. In this vein, Cugusi et al(2017) could not provide a firm conclusion regarding the efficacy of this practice due to the high heterogeneity of the six RCTs analysed in their review.…”
Section: Introductionmentioning
confidence: 99%
“…To the very best of the authors' knowledge, four systematic reviews on the benefits of NW on people with PD have been published so far. Silva et al (2016), offered preliminary conclusions since three out of the five randomised controlled trials (RCTs) reviewed showed a poor methodological quality.…”
Section: Introductionmentioning
confidence: 99%